2018
DOI: 10.1037/pspi0000131
|View full text |Cite
|
Sign up to set email alerts
|

The art of influence: When and why deviant artists gain impact.

Abstract: Some artists rise to fame, while others sink into oblivion. What determines whether artists make an impact? Considering deviance in its sociohistorical context, we propose that artists whose work deviates from their own previous style (intrapersonal deviance) and other artists' styles (interpersonal deviance) gain greater impact than nondeviant artists, as long as deviance is directed toward a progressive style. A preliminary study showed that in western cultures nonrealistic styles are considered more progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 94 publications
(141 reference statements)
5
60
1
1
Order By: Relevance
“…Fourth, we are the first to examine the power-signalling effects of nonconformity among actual recruiters. In contrast to previous studies (Van Kleef et al, 2011;Bellezza et al, 2014;Stamkou et al, 2018), we did not find a direct effect of nonconformity on power perceptions. In fact, our results revealed that nonconformity led to lower (rather than higher) perceptions of power for low-qualified applicants.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Fourth, we are the first to examine the power-signalling effects of nonconformity among actual recruiters. In contrast to previous studies (Van Kleef et al, 2011;Bellezza et al, 2014;Stamkou et al, 2018), we did not find a direct effect of nonconformity on power perceptions. In fact, our results revealed that nonconformity led to lower (rather than higher) perceptions of power for low-qualified applicants.…”
Section: Discussioncontrasting
confidence: 99%
“…In a series of experiments, Van Kleef et al (2011) showed that people who violated a variety of social norms (e.g., by dropping cigarette ashes or putting their feet on the table) were perceived by others as powerful, and were in some cases preferred as leaders (Van Kleef et al, 2012). Research by Stamkou et al (2018) showed that deviant artists are accorded greater influence than artists who conform to prevailing artistic styles. Finally, Bellezza et al (2014) showed that customers dressed in a nonconforming style when entering an elegant boutique, and professors wearing nonconforming attire during a lecture were perceived as more competent than those dressed in a more conforming manner.…”
Section: The Nonconformity Perspective: Nonconformity In Dress Style mentioning
confidence: 99%
See 2 more Smart Citations
“…Other work indicates that norm violators are perceived as powerful (Van Kleef, Homan, Finkenauer, Gündemir, & Stamkou, 2011) and high status (Bellezza, Gino, & Keinan, 2014), and are granted influence when their violations benefit others (i.e., a "Robin Hood effect"; Van Kleef, Homan, Finkenauer, Blaker, & Heerdink, 2012). Furthermore, norm violations may be condoned or even rewarded when norms are relatively unimportant (Brauer & Chekroun;Popa, Phillips, & Robertson, 2014) and their violation is therefore non-threatening, such as in the domain of art (Stamkou, Van Kleef, & Homan, 2018).…”
Section: Journal Of Experimental Social Psychology 84 (2019) 103814mentioning
confidence: 99%